EFAMIX, a tool to decompose inline chromatography SAXS data from partially overlapping components. (22nd November 2021) - Konarev, Petr V.; Graewert, Melissa A.; Jeffries, Cy M.; Fukuda, Masakazu; Cheremnykh, Taisiia A.; Volkov, Vladimir V.; Svergun, Dmitri I.
Abstract: Small‐angle X‐ray scattering (SAXS) is an established technique for structural analysis of biological macromolecules in solution. During the last decade, inline chromatography setups coupling SAXS with size exclusion (SEC‐SAXS) or ion exchange (IEC‐SAXS) have become popular in the community. These setups allow one to separate individual components in the sample and to record SAXS data from isolated fractions, which is extremely important for subsequent data interpretation, analysis, and structural modeling. However, in case of partially overlapping elution peaks, inline chromatography SAXS may still yield scattering profiles from mixtures of components. The deconvolution of these scattering data into the individual fractions is nontrivial and potentially ambiguous. We describe a cross‐platform computer program, EFAMIX, for restoring the scattering and concentration profiles of the components based on the evolving factor analysis (EFA). The efficiency of the program is demonstrated in a number of simulated and experimental SEC‐SAXS data sets. Sensitivity and limitations of the method are explored, and its applicability to IEC‐SAXS data is discussed. EFAMIX requires minimal user intervention and is available to academic users through the program package ATSAS as from release 3.1.